Integration of QUARK and I‐TASSER for Ab Initio Protein Structure Prediction in CASP11. (23rd September 2015) - Zhang, Wenxuan; Yang, Jianyi; He, Baoji; Walker, Sara Elizabeth; Zhang, Hongjiu; Govindarajoo, Brandon; Virtanen, Jouko; Xue, Zhidong; Shen, Hong‐Bin; Zhang, Yang
ABSTRACT: We tested two pipelines developed for template‐free protein structure prediction in the CASP11 experiment. First, the QUARK pipeline constructs structure models by reassembling fragments of continuously distributed lengths excised from unrelated proteins. Five free‐modeling (FM) targets have the model successfully constructed by QUARK with a TM‐score above 0.4, including the first model of T0837‐D1, which has a TM‐score = 0.736 and RMSD = 2.9 Å to the native. Detailed analysis showed that the success is partly attributed to the high‐resolution contact map prediction derived from fragment‐based distance‐profiles, which are mainly located between regular secondary structure elements and loops/turns and help guide the orientation of secondary structure assembly. In the Zhang‐Server pipeline, weakly scoring threading templates are re‐ordered by the structural similarity to the ab initio folding models, which are then reassembled by I‐TASSER based structure assembly simulations; 60% more domains with length up to 204 residues, compared to the QUARK pipeline, were successfully modeled by the I‐TASSER pipeline with a TM‐score above 0.4. The robustness of the I‐TASSER pipeline can stem from the composite fragment‐assembly simulations that combine structures from both ab initio folding and threading template refinements. Despite the promising cases, challenges still exist in long‐range beta‐strand folding, domain parsing, and the uncertainty of secondary structure prediction; the latter of which was found to affect nearly all aspects of FM structure predictions, from fragment identification, target classification, structure assembly, to final model selection. Significant efforts are needed to solve these problems before real progress on FM could be made. Proteins 2016; 84(Suppl 1):76–86. © 2015 Wiley Periodicals, Inc.